2022
DOI: 10.1029/2021gl097601
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐Temporal Clustering of Seismicity Enabled by Off‐Fault Plasticity

Abstract: Earthquakes are a prime example of a complex natural processes with far-from-equilibrium strongly nonlinear dynamics, having substantial societal and economic relevance for large populations worldwide. The lack of quantitative data on timescales capturing multiple large earthquake cycles is a long-standing challenge (Bemis et al., 2021;Scharer & Yule, 2020). Physics-based simulations provide a path to complement the lack of data and to elucidate multi-scale dynamics and spatio-temporal patterns that extend the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 70 publications
2
30
0
Order By: Relevance
“…Even in such an idealized system, we can therefore observe several nested scales of heterogeneities. In a recent paper, (Mia et al., 2022) showed that off‐fault plasticity may lead to partial ruptures as well as temporal clustering of seismic events in an initially homogeneous fault domain, through spatial redistribution of stress. This result is in line with the present findings.…”
Section: Discussionmentioning
confidence: 99%
“…Even in such an idealized system, we can therefore observe several nested scales of heterogeneities. In a recent paper, (Mia et al., 2022) showed that off‐fault plasticity may lead to partial ruptures as well as temporal clustering of seismic events in an initially homogeneous fault domain, through spatial redistribution of stress. This result is in line with the present findings.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluate the impact of these parameters on the complexity of nucleation sites, rupture propagation characteristics, the arrest of individual earthquake events as well as the accumulation of off-fault plasticity during seismic and aseismic phases. We note that other parameters could play a role in the accumulation of off-fault plasticity, such as dilatancy, internal angle of friction and viscosity (Erickson et al, 2017;Mia et al, 2022). We chose to focus primarily on the role of Ψ and c for this initial investigation, as (a) previous modeling of single dynamic ruptures emphasized the importance of those two parameters on the magnitude and accumulation pattern of plastic deformations, (b) The large variability in observational data for those two parameters warrant exploration of a varying parameter space.…”
Section: Objectives Of Present Workmentioning
confidence: 99%
“…Furthermore, dilatancy has been shown to produce minimal impact on plasticity accumulation in dry materials (Templeton & Rice, 2008), and the internal angle of friction is a well constrained parameter over a narrow range between 29° and 35° with an average 32° (Barton & Choubey, 1977). The role of viscosity has been explored in an anti-plane setting by Mia et al (2022), for in-plane deformations we relegate the exploration of the role of viscosity to a future study.…”
Section: Objectives Of Present Workmentioning
confidence: 99%
“…Since their emergence early 2000s, SEAS models have provided crucial insight on several naturally occurring earthquake phenomena such as spontaneous nucleation of earthquakes (Lapusta et al, 2000;Lapusta & Rice, 2003), slow slip events (Barbot, 2019), small repeating earthquakes (Chen & Lapusta, 2009), and seismicity swarms (Zhu et al, 2020). Additionally, advancement in computational tools enabled investigations of the long term affects of thermal pressurization (Noda & Lapusta, 2013), poroelasticity (Torberntsson et al, 2018), quasidynamic slip evolution and fault roughness (Cattania & Segall, 2021;Heimisson, 2020), bi-material effects , low velocity fault zones (Thakur et al, 2020;Abdelmeguid et al, 2019), and inelastic deformations (Erickson et al, 2017;Tal & Faulkner, 2022;Mia et al, 2022) on the evolution of aseismic and coseismic slip. In most elastic models the overall pattern would converge to a statistically steady solution independent of the initial conditions after this transitional spin-up period (Erickson & Jiang, 2018).…”
Section: Previous Modelingmentioning
confidence: 99%
“…Spatial discretisation methods for SEAS generally fall under two main categories: domain-based approaches and boundary integral approaches. The flexibility of domainbased methods allows for handling small-scale heterogeneities, material nonlinearities, as well as complexities of fault geometry (Kuna, 2013;Taborda & Bielak, 2011;Aagaard et al, 2013;Kaneko et al, 2011;Allison & Dunham, 2018;Erickson & Dunham, 2014;Thakur et al, 2020;Barbot, 2019;Mia et al, 2022;Erickson et al, 2017). However, modeling sequences of earthquakes and seismic slip with domain-based methods requires substantial computational effort due to the different spatial, and temporal scales (Tong & Lavier, 2018;Biemiller & Lavier, 2017;Kaneko et al, 2008;Allison & Dunham, 2018;Van Dinther et al, 2013;Mckay et al, 2019;Uphoff et al, 2022).…”
Section: Previous Modelingmentioning
confidence: 99%